Pre-adolescent music listening behaviours on the Cape Flats - Rai, Marcelle Margaret (College of Music, 2024)
This chapter investigates the origin and statement of the problem. It examines the point of departure and theoretical framework for the investigation. The importance of the problem 1s examined. The investigation poses questions which are central to it and proposes a hypothesis for the study. The study focuses on the purpose of the investigation as well as the setting in which the investigation has taken pl ace. The researcher examines the charateristics of the study as well as the research methods employed.